2016
DOI: 10.3847/0004-637x/829/1/28
|View full text |Cite
|
Sign up to set email alerts
|

A BROADBAND X-RAY SPECTRAL STUDY OF THE INTERMEDIATE-MASS BLACK HOLE CANDIDATE M82 X-1 WITH NuSTAR, CHANDRA, AND SWIFT

Abstract: M82 X-1 is one of the brightest ultraluminous X-ray sources (ULXs) known, which, assuming Eddington-limited accretion and other considerations, makes it one of the best intermediate-mass black hole (IMBH) candidates. However, the ULX may still be explained by super-Eddington accretion onto a stellar-remnant black hole. We present simultaneous NuSTAR, Chandra and Swift/XRT observations during the peak of a flaring episode with the aim of modeling the emission of M82 X-1 and yielding insights into its nature. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…We also provide values scaled for P wind = 1 day, whilst, in reality, P wind is a function of spin, mass andṁ0 (via equation 3 -see Figure 4) and so the values shown in Table 1 are only to illustrate values that could be achieved after scaling by the actual observed P wind . QPOs at ∼ 10s of mHz are seen in the ULXs NGC 5408 X-1 (Strohmayer & Mushotzky 2009;Pasham et al 2012), NGC 6946 X-1 (Rao et al 2010), NGC 1313 X-1 (Pasham et al 2015), M82 X-1 (Strohmayer & Mushotzky 2003 -although this may yet be a good candidate for a fairly high mass stellar mass black hole -Brightman et al 2016-or even IMBH -Pasham, Strohmayer & Mushotzky 2014 and claimed in IC 342 X-1 (Agrawal & Nandi 2015). Although longer timescale periodic/quasi-periodic variations (simultaneous with the QPO detection) have yet to be identified in all of these sources, it is apparent that certain combinations of physical parameters would allow their QPOs to be explained by our Lense- Figure 7 but with neutron stars with dipole field strengths of 10 9 G and 10 12 G. The cut off at the magnetospheric radius -which varies witḣ m 0 -is apparent.…”
Section: Are We Seeing the Signature Of Lense-thirring Precession In mentioning
confidence: 99%
“…We also provide values scaled for P wind = 1 day, whilst, in reality, P wind is a function of spin, mass andṁ0 (via equation 3 -see Figure 4) and so the values shown in Table 1 are only to illustrate values that could be achieved after scaling by the actual observed P wind . QPOs at ∼ 10s of mHz are seen in the ULXs NGC 5408 X-1 (Strohmayer & Mushotzky 2009;Pasham et al 2012), NGC 6946 X-1 (Rao et al 2010), NGC 1313 X-1 (Pasham et al 2015), M82 X-1 (Strohmayer & Mushotzky 2003 -although this may yet be a good candidate for a fairly high mass stellar mass black hole -Brightman et al 2016-or even IMBH -Pasham, Strohmayer & Mushotzky 2014 and claimed in IC 342 X-1 (Agrawal & Nandi 2015). Although longer timescale periodic/quasi-periodic variations (simultaneous with the QPO detection) have yet to be identified in all of these sources, it is apparent that certain combinations of physical parameters would allow their QPOs to be explained by our Lense- Figure 7 but with neutron stars with dipole field strengths of 10 9 G and 10 12 G. The cut off at the magnetospheric radius -which varies witḣ m 0 -is apparent.…”
Section: Are We Seeing the Signature Of Lense-thirring Precession In mentioning
confidence: 99%
“…Figure 2 shows the flux as a function of the number of days since 2012-01-01. While the X-ray emission remained at 1-2×10 −11 erg cm −2 s −1 for much of the period covered, the activity increased up to ∼ 5 × 10 −11 erg cm −2 s −1 after ∼ 1150 days and for the rest of the period due to a flaring episode from X-1 (Brightman et al 2016a).…”
Section: Swift/xrt Data Analysismentioning
confidence: 99%
“…Recent NuSTAR results have shown that ULX spectra are often well described with a temperature gradient somewhat shallower than the canonical p=0.75 expected for a thin disk (e.g., Bachetti et al 2013;Brightman et al 2016). Such shallower gradients are expected in sources with very high to super-Eddington luminosities, in which the accretion disk can increase its geometrical thickness due to radiation pressure and advection (Abramowicz et al 1988).…”
Section: The 2014 Epochmentioning
confidence: 99%
“…We follow the description of Soria et al (2015) and Brightman et al (2016). We assume a color correction factor of k = 3 and a geometric factor of x = 0.353, appropriate for the high Eddington fraction of NGC 5907ULX1 (Soria et al 2015).…”
Section: Estimating the Magnetic Field And The Inclinationmentioning
confidence: 99%